2011
DOI: 10.1515/jpem.2011.112
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pubertal gynecomastia, prostate specific antigen, free androgen index, SHBG and sex steroids

Abstract: PSA is a good indicator of androgen activity during puberty. However, owing to FAI remaining as the single significant variable for pubertal gynecomastia, we suggest that it is still the best parameter to elucidate the etiopathogenesis of gynecomastia as well as other pubertal developmental abnormalities in male adolescents, and further longitudinal studies are needed to investigate the relationships between PSA and FAI in puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 31 publications
6
13
0
1
Order By: Relevance
“…found significantly increased BMI and weight in young adult males (19–29 year) with gynaecomastia and also found a significantly larger sum of all skin folds in subjects with gynaecomastia. The link between body size and the development of gynaecomastia is hypothesized to be increased aromatization in adipose tissue causing an androgen‐oestrogen imbalance . Our failure to demonstrate such an imbalance, nevertheless, does not rule out the possibility of a local change in aromatization in the breast tissue in boys with gynaecomastia.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…found significantly increased BMI and weight in young adult males (19–29 year) with gynaecomastia and also found a significantly larger sum of all skin folds in subjects with gynaecomastia. The link between body size and the development of gynaecomastia is hypothesized to be increased aromatization in adipose tissue causing an androgen‐oestrogen imbalance . Our failure to demonstrate such an imbalance, nevertheless, does not rule out the possibility of a local change in aromatization in the breast tissue in boys with gynaecomastia.…”
Section: Discussionsupporting
confidence: 93%
“…In our population‐based study of healthy school boys and adolescents, we found that 23% of all pubertal boys had gynaecomastia. More specifically, 63% of boys in genital stage 4 had gynaecomastia which is in accordance with the prevalence reported in previous studies which vary from 40% to 60% . Importantly, we found significantly higher IGF‐I levels in boys with gynaecomastia even after adjustment for confounders.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations